Adherence to Infection Prevention and Control Measures Among Health-Care Workers Serving in COVID-19 Treatment Centers in Punjab, Pakistan. (14th February 2023) - Mustafa, Zia Ul; Majeed, Hafiza Kiran; Latif, Shaiza; Salman, Muhammad; Hayat, Khezar; Mallhi, Tauqeer Hussain; Khan, Yusra Habib; Khan, Amer Hayat; Abubakar, Usman; Sultana, Kishwar; Godman, Brian
Abstract: Objective: Infection prevention and control (IPC) measures are easily adoptable activities to prevent the spread of infection to patients as well as among health-care workers (HCWs). Methods: This cross-sectional study evaluated the adherence to IPC measures among HCWs working at coronavirus disease 2019 (COVID-19) treatment centers in Punjab, Pakistan. HCWs were recruited by means of convenient sampling through Google Form ® using the World Health Organization risk assessment tool. All data were analyzed using SPSS 20. Results: A total of 414 HCWs completed the survey (response rate = 67.8%), and majority of them were males (56.3%). Most of the HCWs were nurses (39.6%) followed by medical doctors (27.3%). Approximately 53% reported insufficiency of personal protective equipment (PPE), 58.2% did not receive IPC training and 40.8% did not have functional IPC team at their health facilities. The majority of HCWs (90%) used disposable gloves and N95 facemasks while interacting with COVID-19 patients. Nearly 45% used protective face shields and gowns before providing care to their patients. Hand hygiene practices while touching, and performing any aseptic procedure was adopted by 70.5% and 74.1% of HCWs, respectively. Conclusions: In conclusion, the adherence to IPC measures among Pakistani HCWs working in COVID-19 treatment centers is good despite the limited availability of PPEs. Their practices can be optimized by establishing institutional IPC teams, periodic provision of IPC training, and necessary PPE.